Biosensors Show the Pharmacokinetics of S-Ketamine in the Endoplasmic Reticulum - Bera, Kallol; Kamajaya, Aron; Shivange, Amol V.; Muthusamy, Anand K.; Nichols, Aaron L.; Borden, Philip M.; Grant, Stephen; Jeon, Janice; Lin, Elaine; Bishara, Ishak; Chin, Theodore M.; Cohen, Bruce N.; et al. (Frontiers in Cellular Neuroscience, 2019)
The target for the “rapid” (< 24 h) antidepressant effects of S-ketamine is unknown, vitiating programs to rationally develop more effective rapid antidepressants. To describe a drug’s target, one must first understand the compartments entered by the drug, at all levels—the organ, the cell, and the organelle. We have therefore developed molecular tools to measure the subcellular, organellar pharmacokinetics of S-ketamine. The tools are genetically encoded intensity-based S-ketamine-sensing fluorescent reporters, iSKetSnFR1 and iSKetSnFR2. In solution, these biosensors respond to S-ketamine with a sensitivity, S-slope = delta(F/F0)/(delta[S-ketamine]) of 0.23 and 1.9/microM, respectively. The iSketSnFR construct allows measurements at < 0.1 µM S-ketamine. The iSKetSnFR1 and iSKetSnFR2 biosensors display > 100-fold selectivity over other ligands tested, including R-ketamine. We targeted each of the sensors to either the plasma membrane (PM) or the endoplasmic reticulum (ER). Measurements on these biosensors expressed in Neuro2a cells and in human dopaminergic neurons differentiated from iPSCs show that S-ketamine enters the ER within a few s after appearing in the external solution near the PM, then leaves as rapidly after S-ketamine is removed from the extracellular solution. In cells, S-slopes for the ER and PM-targeted sensors differ by < 2-fold, indicating that the ER [S-ketamine] is less than 2-fold different from the extracellular [S-ketamine]. Organelles represent potential compartments for the engagement of S-ketamine with its antidepressant target, and potential S-ketamine targets include organellar ion channels, receptors, and transporters.